Two-step passivation for enhanced InGaN/GaN light emitting diodes with step graded electron injectors. (January 2018) - Sheremet, V.; Genç, M.; Gheshlaghi, N.; Elçi, M.; Sheremet, N.; Aydınlı, A.; Altuntaş, I.; Ding, K.; Avrutin, V.; Özgür, Ü.; Morkoç, H.
Abstract: Enhancement of InGaN/GaN based light emitting diode performance with step graded electron injectors through a two-step passivation is reported. Perimeter passivation of LED dies with SiO2 immediately following ICP mesa etch in addition to conventional Si3 N4 dielectric surface passivation leads to decrease in the reverse bias leakage current by a factor of two as well as a decrease in the shunt current under forward bias by an order of magnitude. Mitigation of the leakage currents owing to the two-step passivation leads to significant increase in the radiant intensity of LEDs by more than a factor of two compared to the conventional single step surface passivation. Further, micro-dome patterned surface of Si3 N4 passivation layer allow enhanced light extraction from LEDs. Highlights: Si3 N4 is one of the best passivation material for front emitting GaN based LEDs. Two-step passivation include perimeter passivation of LED dies after ICP mesa etch. Perimeter passivation decreases the reverse bias leakage current by factor of two. Two-step passivation results in two times increase in the radiant intensity of LED. Micro-dome patterned surface of Si3 N4 passivation layer enhance efficiency of LEDs.